Connecting heterogeneous agents under incomplete information - Masaki Aoyagi (Osaka University, Institute of Social and Economic Research (ISER), 2020)
This paper studies the problem of a monopolistic platform which offers agents connection with one another. Agents have heterogeneous characteristics that are valued by some other agents and observed privately by the principal. The agents are privately informed about their heterogeneous preferences over the characteristics of the other agents. The platform solicits information from the agents about their preferences and then offers an allocation that consists of groups of connected agents and subscription fees. We study mechanisms which induce truthful reporting and acceptance of the proposed allocation as a unique equilibrium outcome. We identify asymptotically optimal mechanisms which fully extract the agents' informational rents in the limit as the market becomes large.
Keywords: D42; D47; D62; D82; L12; 330; platform; network externalities; random graph; revenue maximization; strategy-proof